CURRENT TRENDS IN INDIAN EDUCATION SYSTEM - A REVIEW - Nargis Rashid; Bilal Ahmad Mir (RADJA PUBLIKA, 2023)
The aim of the study is to examine the current trends in educational system in India. Type of this study is literature review. Content analysis is applied to collect the data. Education is important for a country like India for its development and economic growth as well as social development. It typically comprises under graduate, post graduate degrees as well as pre - doctoral and doctoral programmes. It also plays an important role in producing teachers for the field of education. Therefore, it is essential for survival. Hence, this study gives an insight into the current trends in the Indian education system, challenges faced by it, and methods to improve it. The study setting is a review and the information is obtained through search engines like PubMed and google scholar by searching for keywords and the study was made. In Spite of the significant growth of higher education in the past few years, it is still in a danger zone due to several challenges like the quota system, privatization, etc. Hence , various methods need to be found to improve the higher education system in India.